Dampak Dinasti Politik Terhadap Culture Demokrasi Pancasila di Indonesia - Khalib Gadafi; Sasmi Nelwati (STIKes Ibnu Sina Ajibarang, 2024)
Abstract This article examines the development of political dynasties in Indonesia and their impact on Pancasila democracy. The phenomenon of dynastic politics at the local level, which is increasingly prevalent in various regions of Indonesia, is the background of this discussion. The emergence of politics under this dynasty presents various positive and negative aspects, which reflect the dynamics of the political culture of Indonesian society in politics and democracy. Families maintain power by placing their members in strategic positions in the formal (government) and informal (business or project) sectors. The history of Indonesian governance shows the existence of political dynasties that last for years. If not addressed, these political dynasties can flourish, creating pros and cons amidst the implementation of Pancasila democratic governance. This research aims to explore the implementation of governance in Indonesia and understand how political dynasties affect the development of Pancasila democracy in the country.